Dialectic of Religion and National Identity in North Sulawesi Jewish Communities in The Perspective of Cross-Cultural and Religious Psychology - Sekar Ayu Aryani (Al-Jami'ah: Journal of Islamic Studies, 2022)
This study aims to explore how theology and culture influence the national attitude and behavior of Jews in North Sulawesi. The question arises because of Judaism teaching on Promised Land, an always-longed place by the Jews of the diaspora country. The qualitative study employs purposive sampling by using the Cross-Cultural and Religious Psychology approach. It relied on interviews from Jews prominent figures and its followers in North Sulawesi and was complemented by the non-Jews religious leader, documents, and literature. Data analysis consists of data reduction, exploration, and verification. The last step was data contextualization by combining field and library research data. The study found that Jews in North Sulawesi harbored a longing for the Promised Land, but it did not prevent the growth of their nationalism spirit and loyalty to the Republic of Indonesia. Furthermore, their firm nationalism to Indonesia, and the objective approach to the Promised Land proofing their loyalty to the Torah. This research also discovered, behind the exclusive impression of Jews, their teachings there had a very pluralist and inclusive vision. The study concludes, the assumption that Jews in North Sulawesi will face loyalty problem to the Republic of Indonesia appear unproven, because they can interpret their faith flexibly and rationally.  [Penelitian ini bertujuan untuk mengeksplorasi bagaimana teologi dan budaya mempengaruhi sikap dan perilaku nasionalisme orang Yahudi di Sulawesi Utara. Pertanyaan itu muncul karena Yudaisme memiliki ajaran tentang Tanah Perjanjian, tempat yang selalu dinanti oleh orang-orang Yahudi di negara diaspora. Penelitian kualitatif ini menggunakan purposive sampling dengan menggunakan pendekatan Psikologi Lintas Budaya dan Agama. Pengumpulan data mengutamakan wawancara dari tokoh-tokoh Yahudi dan pengikutnya di Sulawesi Utara dan para tokoh agama non-Yahudi, kemudian dilengkapi dengan dokumen, dan studi literatur. Analisis data terdiri dari reduksi data, eksplorasi, dan verifikasi. Langkah terakhir adalah kontekstualisasi data dengan menggabungkan data penelitian lapangan dan perpustakaan. Studi ini menemukan bahwa orang-orang Yahudi di Sulawesi Utara menyimpan kerinduan akan Tanah Perjanjian, tetapi itu tidak menghalangi pertumbuhan semangat nasionalisme dan kesetiaan mereka kepada Republik Indonesia. Lebih jauh lagi, nasionalisme mereka yang kuat terhadap Indonesia, dan pendekatan objektif terhadap Tanah Perjanjian membuktikan kesetiaan mereka kepada Taurat. Penelitian ini juga menemukan, di balik kesan eksklusif orang Yahudi, ajaran mereka di sana memiliki visi yang sangat pluralis dan inklusif. Studi ini menyimpulkan, anggapan bahwa orang Yahudi di Sulawesi Utara akan menghadapi masalah kesetiaan kepada Republik Indonesia tampaknya tidak terbukti, karena mereka dapat menafsirkan iman mereka secara fleksibel dan rasional.]